Pyrolysis of Napier Grass in a Fixed Bed Reactor: Effect of Operating Conditions on Product Yields and Characteristics - Mohammed, I.Y. (North Carolina State University, 2015)
This study presents a report on pyrolysis of Napier grass stem in a fixed bed reactor. The effects of nitrogen flow (20 to 60 mL/min), and reaction temperature (450 to 650 °C) were investigated. Increasing the nitrogen flow from 20 to 30 mL/min increased the bio-oil yield and decreased both bio-char and non-condensable gas. 30 mL/min nitrogen flow resulted in optimum bio-oil yield and was used in the subsequent experiments. Reaction temperatures between 450 and 600 °C increased the bio-oil yield, with maximum yield of 32.26 wt at 600 oC and a decrease in the corresponding bio-char and non-condensable gas. At 650 °C, reductions in the bio-oil and bio-char yields were recorded while the non-condensable gas increased. Water content of the bio-oil decreased with increasing reaction temperature, while density and viscosity increased. The observed pH and higher heating values were between 2.43 to 2.97, and 25.25 to 28.88 MJ/kg, respectively. GC-MS analysis revealed that the oil was made up of highly oxygenated compounds and requires upgrading. The bio-char and non-condensable gas were characterized, and the effect of reaction temperature on the properties was evaluated. Napier grass represents a good source of renewable energy when all pyrolysis products are efficiently utilized. © 2015. All Rights Reserved.